2021
DOI: 10.3389/fonc.2021.694821
|View full text |Cite
|
Sign up to set email alerts
|

Inexpensive Systemic Inflammatory Biomarkers in Ovarian Cancer: An Umbrella Systematic Review of 17 Prognostic Meta-Analyses

Abstract: The association of several inflammation-based biomarkers [lymphocyte-to-monocyte, neutrophil-to-lymphocyte, and platelet-to-lymphocyte ratios (LMR, NLR, and PLR, respectively)] with the survival of epithelial ovarian cancer (EOC) patients has been extensively investigated in several systematic reviews and meta-analyses (MAs) of observational studies. The aim of this umbrella systematic review is to appraise all available results in published MAs that explored the association between these biomarkers and EOC ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 74 publications
2
11
0
Order By: Relevance
“…According to a meta‐analysis in 2014, a high NLR was a poor predictive factor for OS among various disease subgroups and across disease stages of 100 studies comprising 40 559 patients and a high NLR was significantly associated with OS, similar to the present study. Although the role of PLR requires a meta‐analysis of randomized trials, previous studies showed that a high PLR was an independent predictor of poor OS for epithelial ovarian cancers 49 . To date, several studies focused on the role of NLR, PLR, and SII in thymic epithelial tumors 23–25,50–53 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to a meta‐analysis in 2014, a high NLR was a poor predictive factor for OS among various disease subgroups and across disease stages of 100 studies comprising 40 559 patients and a high NLR was significantly associated with OS, similar to the present study. Although the role of PLR requires a meta‐analysis of randomized trials, previous studies showed that a high PLR was an independent predictor of poor OS for epithelial ovarian cancers 49 . To date, several studies focused on the role of NLR, PLR, and SII in thymic epithelial tumors 23–25,50–53 .…”
Section: Discussionmentioning
confidence: 99%
“…Although the role of PLR requires a meta‐analysis of randomized trials, previous studies showed that a high PLR was an independent predictor of poor OS for epithelial ovarian cancers. 49 To date, several studies focused on the role of NLR, PLR, and SII in thymic epithelial tumors. 23 , 24 , 25 , 50 , 51 , 52 , 53 In 2021, Huang et al established a nomogram to predict outcomes of thymomas by combining clinical features, NLR, PLR and other blood assays but PLR was not an independent prognostic factor, rather the primary outcome indicator was relapse‐free survival rather than OS.…”
Section: Discussionmentioning
confidence: 99%
“…86,87 The involvement of lymphocytes in the defense against cancer cells, scientifically justifies their use in medical practice, the numerical value being involved in the calculation of the three ratios: NLR, MRL, and PLR. 13,71,73,88 Platelets, as a factor involved in the defense system through the development of antineoplastic inflammation. Physiopathologically, in neoplasms, the research in daily medical practice of the number of circulating platelets, their volume and the calculation of the PLR index, is supported by the involvement of these elements figured in:…”
Section: The Relationship Between the Chronic Inflammatory Process An...mentioning
confidence: 99%
“…Scores based on absolute values of different types of leukocytes are NLR-neutrophil-to-lymphocyte ratio, PLR-platelet-to-lymphocyte ratio, and LMR-lymphocyte-to-monocyte ratio. [11][12][13][14]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the association of three inflammation-based parameters with the survival of OC patients has been proposed, i.e., lymphocyte/monocyte ratio (LMR) (a), neutrophil/lymphocyte ratio (NLR) (b), and platelet/lymphocyte ratio (PLR) (c). High NLR and PLR and low LMR were independent prediction factors of poor OS and PFS in OC ( 147 ).…”
Section: Peripheral Immunome Of Ovarian Cancermentioning
confidence: 99%